It’s not easy to relax: liveness in chained BFT protocols - Abraham, Ittai; Crooks, Natacha; Giridharan, Neil; Howard, Heidi; Suri-Payer, Florian (International Symposium on Distributed Computing (DISC), 2022)
Modern chained BFT SMR protocols have poor liveness under failures as they require multiple consecutive honest leaders to commit a single block. Siesta, our proposed new BFT SMR protocol, is instead able to commit a block that spans multiple non-consecutive honest leaders. Siesta reduces the expected commit latency of HotStuff by a factor of three under failures, and the worst-case latency by a factor of eight.
Brief Announcement